ANALYSIS OF THE EFFECT OF SERVICE QUALITY, BRAND IMAGE, AND PRICE ON CUSTOMER SATISFACTION - Putri, Indrianingsih; Rahayu, Jekti; Murtaliningtyas, Wenny (Univesitas Muhammadiyah Tangerang, 2024)
Technological advances have had a positive impact on society, for example making interaction easier, sharing information and making it easier for people to fulfill various needs in their lives. The company that is taking advantage of this opportunity is Shopee, through the ShopeeFood service feature in its application, users can order food which will later be delivered by a courier. This research aims to determine the influence of Service Quality, Brand Image, and Price on ShoppeFood Consumer Satisfaction in Jember. This type of research is quantitative. The population in this study were all ShoppeFood users in Jember using the Ferdinand formula sampling technique. The data source in this research uses primary data, namely questionnaires. Data were analyzed using multiple linear regression, normality test, multicollinearity test, heteroscedasticity test, t test, f test, and determination test which were carried out computationally using the SPSS program. The results of this research show that Service Quality, Brand Image, and Price have a positive and significant effect on consumer satisfaction of ShoppeFood users in Jember.